The Pedagogical Model of Hybrid Teaching: Difficulties of University Students in the Context of COVID-19 - Alejandro Lorenzo-Lledó; Asunción Lledó; Alba Gilabert-Cerdá; Gonzalo Lorenzo (MDPI AG, 2021)
The global pandemic caused by COVID-19 has led to changes in many areas, with educational scenarios being affected. In this sense, university education has undergone significant changes owing to the impossibility of following the fully face-to-face mode of teaching. Given this situation, the general objective of this study is to analyze the university educational scenario in the context of COVID-19 and, more specifically, to identify the difficulties perceived by students. Using a mixed quantitative-qualitative methodological approach, an ad hoc questionnaire was designed, and data were collected from a sample of 238 students of the Bachelor's Degree in Teaching during the 2020/2021 academic year. The results obtained have shown that students have experienced numerous difficulties in adapting to the hybrid teaching model. In this sense, it is worth highlighting the decrease in motivation, the feeling of loneliness, technical connection problems, and less interaction with the teaching staff and other students. The degree of satisfaction with the teaching received is also moderate. As a conclusion, it can be stated that the difficulties identified recommend the introduction of actions to improve the application of the teaching model implemented in favor of university excellence.